Analisis Prioritas Pengembangan Moda Transportasi Umum Di DKI Jakarta - Suryobuwono, Abdullah Ade; Raga, Paulus; Nugroho, Aditya; Tampubolon, Irvan Adam; Basalamah, Zahira Aura Rahma; Irenita, Novembriani (Institut Transportasi dan Logistik Trisakti, 2021)
Transportation is the main actor that is needed in the mobility activities of the people of DKI Jakarta in meeting the needs of the community. People's behavior in making a trip is something that cannot be avoided, one of which is avoiding city congestion. Transportation facilities and infrastructure, such as Transjakarta Buses and Commuter Lines for both within and between cities, need to be developed to reduce traffic accidents. The purpose of this research is to find out whether transportation services can be used properly in a fast time and at the right price and with optimal service, to know a good strategy to avoid negative impacts on the use of public transportation and to know the optimal performance in policies whose purpose is to protect public transportation. and provide a sense of security to users of public transportation. In this study, the analytical hierarchy process (AHP) method was used. The results of this study indicate that the order of priority for the development of public transportation modes in DKI Jakarta is Mass Rapid Transit (MRT), Light Rail Transit (LRT), Commuter Line (CL) and Transjakarta or Bus Rapid Transit (BRT) based on the criteria of cost, travel time, comfort, security, ease of access and medical.